The Impact of Perceived Ease of Use towards Perceived Enjoyment and Customer Experience to Customer Satisfaction and Repurchase Intention (Case Study Among Spotify Premium Users) - Cutriani Sari, Fidiyah B1024161018 (Equator Journal of Management and Entrepreneurship (EJME), 2020)
The purpose of this research is to analyze the impact of Perceived Ease of Use towards Perceived Enjoyment and Customer Experience to Customer Satisfaction and Repurchase Intention. The digital world offers many business opportunities to companies that run platforms turning web-users into subscribers. The high trend of digital music distribution affects music sales in the physical form, seen from the income which decreases from year to year. From this point we can see that it is undeniable Customer Satisfaction and Repurchase Intention plays an important factor in music streaming service. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software.The hypothesis of the research are H1:Perceived Ease of Use has a positive effect to Perceived Enjoyment, H2: Perceived Ease of Use has a positive effect to Experience, H3: Perceived Enjoyment has a positive effect to Customer Experience, H4: Perceived Enjoyment has a positive effect to Customer Satisfaction, H5: Customer Experience has a positive effect to Customer Satisfaction, H6: Customer Satisfaction has a positive effect to Repurchase Intention. H7: Perceived Enjoyment mediates the relationship between Perceived Ease of Use and Customer Satisfaction. H8: Customer Experience mediates the relationship between Perceived Ease of Use and Customer Satisfaction. H9: Customer Satisfaction mediates the relationship between Perceived Enjoyment and Repurchase Intention. H10: Customer Satisfaction mediates the relationship between Customer Experience and Repurchase Intention. The result of this research shows that H1, H3, H4, H5, H6, H7, H9 and H10 are accepted but H2 and H8 are rejected.Keyword: Perceived Ease of Use, Perceived Enjoyment, Customer Experience, Customer Satisfaction, Repurchase IntentionReferences:Traver, L. &. (2017). E-Commerce 2017, 13th Edition. Pearson.McCourt T., & P., B. (2003). When Creators, Corporations and Consumers Collide: Napster and The Development of On-line Music Distribution. Media, culture & society 25(3), 333-350.Viviero, & Nakano. (2008). Cadeia de produção da indústria fonográfica e as gravadoras independentes.Davis F D, Bagozzi R P, & R., W. P. (1992). .Extrinsic and Intrinsic Motivation to Use Computers in the Workplace. Journal of Applied and Social Psychology, 22(14):1111-1132.Davis, F. D. (1989). Perceived Usefulness, Perceived Ease of Use, and User Acceptance of Information Technology. IT usefulness and ease of use, 4.Lovelock, C., & Wright., H. L. (2011). Manajemen Pemasaran Jasa. Jakarta: PT. Indeks (Gramedia Group).Lu, C. L., Chang, H.-H., & Yu, S.-T. (2013). Online Shoppers: Perceptions of E-retailers’ ethics, cultural orientation, and loyalty. An Exploratory study in Taiwan, Internet Research, and Vol. 23 Issue: 1,, 47-68.Kotler, P., & Keller, K. L. (2012). Marketing Management. Harlow, Boston MA: Pearson Education.Sugiyono. (2014). Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif, dan R&D